Shakespeare on love : the sonnets and plays in relation to Plato's Symposium, alchemy, Christianity and renaissance neo-platonism /: the sonnets and plays in relation to Plato's Symposium, alchemy, Christianity and renaissance neo-platonism. (2011) - Unknown
No abstract available